KARAKTERISASI PATOGEN HAWAR DAUN BAKTERI SECARA FENOTIPIK PADA BAWANG MERAH (ALLIUM CEPA L. KELOMPOK AGGREGATUM) - Asrul Asrul; Triwidodo Arwiyanto; Bambang Hadisutrisno; Jaka Widada (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
The research aimed at determining the types of pathogen associated with bacterial leaf blight diseases of shallots. The bacteria were isolated and characterized based on the  morphological, biochemical and physiological morphology of their colony and cell.  There were eight isolates of pathogenic bacteria from pure culture.  Generally, the isolates have Gram-negative characters, short rod-shaped cells, have peritrikus flagellum and mucoid, yellow or beige colonies, round, convex or flat forms, and is shiny. The isolates react positively to catalase, urease, levan, indole production, and tween 8 tests. They also can live at temperature between 20 – 370C, pH 5 – 7 and tolerant to NaCl content ranging from 0 – 8.5%. The isolates react negatively to oxidases, reduce nitrates, fluorescent pigments, arginine, gelatin and starch.  Based on these characteristics, the isolates found generally have a closer resemblance to the properties of P. ananatis with a similarity coefficient of 88%  than bacteria X. axonopodis pv. allii with a similarity coefficient of 78%.  The symptoms appeared in the plant leaves were wilted (water soaked), shrinking, curving down, chlorosis, necrosis, and dieback.